A novel method for evaluating correlation functions in lattice hadron spectroscopy - Peardon, Michael (My University, 2010)
We describe a new approach for evaluating hadronic correlation functions which combines Laplacian-Heaviside quark smearing with a stochastic estimator of quark propagators. This method utilizes noise dilution in a new way to reduce the variance in correlators. The efficacy of the new algorithm is demonstrated on a number of systems, including disconnected diagrams and multi-hadron correlators, on a small lattice where comparisons with the results obtained with exactly determined quark propagators are possible. On larger lattice volumes, the use of exact propagators becomes prohibitively expensive, while the stochastic method is still computationally feasible.
Proceedings of The XXVIII International Symposium on Lattice Field Theory
The XXVIII International Symposium on Lattice Field Theory
Keywords: Hadronic correlation functions; Stochastic methods; Exact propagators; Quark propagators